Modification of the existing maximum residue level for bifenazate in soya bean. (20th September 2017) - ,; Brancato, Alba; Brocca, Daniela; De Lentdecker, Chloe; Erdos, Zoltan; Ferreira, Lucien; Greco, Luna; Janossy, Judit; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; Lythgo, Christopher; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Arysta LifeScience Great Britain Ltd submitted a request to the competent national authority in Italy to set new maximum residue level (MRL) for the active substance bifenazate in soya beans. The data submitted in support of the request were found to be sufficient to derive a MRL proposal for soya beans. Adequate analytical methods for enforcement are available to control the residues of bifenazate and its metabolite in the commodity under consideration. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of bifenazate according to the reported agricultural practice is unlikely to present a risk to consumer health.